2014
DOI: 10.1007/s11999-014-3497-x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Age-related Cervical Disc Degeneration in the Sand Rat

Abstract: Background Disc space narrowing, osteophytes, and disc degeneration are common and increase with aging. Few animal models are appropriate for the study of spontaneous age-related cervical disc degeneration. Questions/purposes We used the sand rat, a member of the gerbil family with well-recognized age-related lumbar disc degeneration, to determine whether spontaneous cervical disc degeneration differed from lumbar degeneration when evaluated by (1) radiologic and (2) histologic measures. Animals 2 to 25 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…Cervical disc space narrowing, osteophytes, and disc degeneration are common and increase with aging [ 9 ]. The prevalence of abnormal magnetic resonance images of the cervical spine is related to age in asymptomatic individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cervical disc space narrowing, osteophytes, and disc degeneration are common and increase with aging [ 9 ]. The prevalence of abnormal magnetic resonance images of the cervical spine is related to age in asymptomatic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al [ 4 ] reported that T1 sagittal slope angle decreased in the older group, as compared with the younger counter part. Many studies have evaluated the factor of cervical disc degeneration [ 1 5 6 7 8 9 10 11 ]. However, there are no studies on the relationship between T1 slope and cervical spondylosis.…”
Section: Introductionmentioning
confidence: 99%
“…Aging is thought to be a cause leading to disc degeneration [81,82]. Autophagy has also been shown to change with aging [83,84].…”
Section: Changes Of Autophagy In Degenerative Ivd Cellsmentioning
confidence: 99%
“…94 Besides size, the second difference between animal models is that in most animals, degeneration needs to be induced, since this is not a spontaneously occurring phenomenon. Exceptions are the sand rat 95,96 and the dog, 70 in which IVD degeneration occurs spontaneously with aging and is, at least in the dog, a clinical entity. 97 In small animals, IVD degeneration can be induced by genetic modification, 74,76,98 partial NP removal, 99 IVD puncture, 100-102 compression 103,104 (eg, tail-looping 105 ) and even whole body vibration.…”
Section: Differences In Ivds Between Human and Animal Species Includementioning
confidence: 99%